Understanding measles virus: from isolation to immunological cellular mechanisms and immunisation 1954–2024 - Brent Brown; Chinua Imarogbe; Ingo Fricke (Exploration of Immunology)
Measles virus (Morbillivirus abbreviated as MV, but more recently MeV) is the causal agent of measles disease, thought to have existed at least 4,000 years ago, affecting predominantly infants, but also immunocompromised individuals remaining a public health issue today globally. In this review, we discuss the historical background about MeV infection to modern-day research on measles disease, current epidemiology, but also what is known about immunisation against it. We report what is known about the viral structure and the function of the viral proteins. This additionally covers the cellular structure of MeV, mechanisms, and clinical aspects of infection. Including a review of topics like cellular receptor-associated entry factors, to the immunology of MeV infection. In this review, the current knowledge of innate immune responses during infection is explained, which involves changes to chemokine and cytokine expression, finalised by the present understanding of adaptive immune responses to MeV. The genomic stability of the MeV proteins is explained and suggestive that it could be the third pathogen with eradication potential (after the variola and rinderpest viruses). Further biological and immunological clarification as to how this could occur is explained below.